yes, m is the gradient in y = mx + c ....the equation of a line. So let's find that form. you started but you didn't finish.

4x - 3y + 5 = 0

=> 3y = 4x + 5

=> y = (4/3)x + 5/3 ........divided both sides by 3

Now we can clearly see that the gradient is 4/3

now remember:(ii) Find an equation of the linel2which passes through the point (1,2) and which is perpendicular to the linel1giving your answer in the form ax+by+c=0

(1) two straight lines are parallel if they have the same gradient

(2) two straight lines are perpendicular if their gradients are negative inverses of each other (that means if you take one gradient, turn it upside down by putting 1 over it, and put a minus sign in front, you get the other gradient)

now we want a line perpendicular to l1. the gradient of l1 is 4/3, so the gradient of the line we want is -3/4

using m = -3/4, (x,y) = (1,2), we have:

y = mx + c

=> 2 = (-3/4)(1) + c

=> c = 2 + 3/4 = 11/4

so our line is y = (-3/4)x + 11/4

or (3/4)x + y - 11/4 = 0

Just in case you are familiar with the point-slope form, we could find the equation of the line directly.

using m = -3/4 and (x1,y1) = (1,2), by the point slope form we have:

y - y1 = m(x - x1)

=> y - 2 = (-3/4)(x - 1)

=> y - 2 = (-3/4)x + 3/4

=> (3/4)x + y - 2 - 3/4 = 0

=> (3/4)x + y - 11/4 = 0